A INTERAÇÃO ENTRE SURDOS: FUNÇÕES DOS MARCADORES DISCURSIVOS EM LIBRAS - Sheyla Cristina Araujo Matoso Silva (2022)
Despite the growth of works that discuss the linguistic and functional aspects of sign languages, those are still scarce when compared to other oral languages. In this vein, the aim of this research is to analyze the use of discourse markers in Brazilian sign language (Libras) and the functions they play in the interaction among deaf people. The theoretical framework is based on the studies of Conversation Analysis, developed mainly by Marcuschi (1989; 2003), Preti (2000; 2002; 2003; 2005), Castilho (1989; 1994; 2020), Urbano (1999), Barros (2005), Fraser (1994), Galembeck and Blanco (2001), Koch and Barros (1997), Risso, Silva and Urbano (2015) and Schiffrin (1987). Concerning the field of Libras, we highlight the works of Gesser (2009; 2012), Quadros (2013; 2019), Quadros and Karnopp (2004) and Leite (2008), among other authors who develop renowned studies in both areas above-mentioned. The corpus of this research is composed of videos available on the Internet by the project of Federal University of Santa Catarina called Corpus de Libras. Regarding the methodological procedures for data transcription, we used the ELAN software (Eudico Language Annotator) developed by the Max Plank Institute, which allows the segmentation and analysis of videos in a more detailed way and provides some resources that contribute to the process of transcription and translation of sign language. Thus, we chose to select the videos that presented free discursive topics in order to analyze conversation in Libras in a more spontaneous way. After examining and choosing the videos, we transcribed and translated the excerpts into Portuguese. Our data analysis shows that both libras and oral languages have discourse markers with defined functions during a communicative event: they act in the organization, structuring and articulation of the text, add dynamicity to the dialogue and contribute to the construction and management of the conversational act. According to the findings obtained by means of the analysis of dialogues in pairs, consisting of 22 (twenty-two) selected videos, we indicate 85 (eighty-five) occurrences, pointing out the moment where those linguistic elements were activated by the signers of Libras. Among all the examples, we observed a higher frequency of markers related to the ideational function, which allude to the text organization during signaling, totaling 60 (sixty) times in this function and 25 (twenty-five) in the interactional function. It is important to highlight that, as in oral languages, interactants employ those linguistic elements in Libras based on their objectives in the conversational act, such as: listener’s involvement, search for discourse approval, verbal planning, expression of opinion, linguistic mitigation and movement of discursive topics. Therefore, this study contributes to language studies regarding the organization of speech by deaf people who are fluent in Libras and the use of discourse markers in different contexts of use. Keywords: Discourse Markers, Libras, Deaf People.